Meningkatan Minat Belajar dan Fokus Peserta Didik dalam Pembelajaran Matematika Kelas II SDN 09 Bilah Barat - Julianti Marpaung; Kharisma Pratidina (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
The low interest of students in mathematics lessons results in most students being less enthusiastic about following the lessons given by the teacher, so that student learning outcomes are low. With this situation, teachers will try their best to improve learning patterns by conducting classroom action research (CAR). The purpose of this study is to increase student interest and learning outcomes in mathematics, the main material explains the addition and subtraction of decimal numbers in writing using the experimental method carried out in class II SDN.09. BILAH BARAT which consists of 18 students. From the research that I conducted for 2 cycles, and based on all the discussions and analyses that I have done, it is concluded that learning with the experimental method has a positive impact on improving student learning achievement with an increase in student learning completeness in each cycle, namely cycle one (65.22%), and cycle 2 (78.26%). The use of the experimental method has a positive influence, namely increasing student learning motivation, this can be seen from the results of the interview which stated that students were interested and interested in the experimental method so that they were motivated to learn.